Influências geográficas na composição físico-química e fitoquímica do pólen de abelhas nativas da Região Oeste do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
Pollen is the main nutrient and protein source for bees and its composition depends on the region or season, geographic location, vegetation species, soil, climate, water and botanical identity. Despite the growing demand for stingless Brazilian bee products, their nutritional and bioactive properties are underestimated. Thus, this paper aims to determine the physicochemical and phytochemical characteristics of pollen collected by stingless bees from Western of Pará. For the physicochemical evaluation, the parameters areaccording to the Technical Regulation (RT) of quality for agricultural pollen. The results confirmed differences in the physicochemical composition of the stored pollen of several studied species. Species 01 presented high values for humidity and protein; species 02, showed low values for nutritional components, but for the ash content value, presented good results in relation to other species. Species 03 showsaverage results, however, low to ashes content values. For the carbohydrate composition, all samples were in accordance with the values determined by RTB for bee pollen. Regarding bioactive compounds (phenolic content, flavonoid content and antioxidant capacity evaluation by DPPH free radical sequestration) presents a low variation, which the poles collected by bees 01 and 06, obtain the best values. It has concluded that the nutritional and bioactive components found in the pole do not have significant importance in the several pollen sources for collection of native bees, due to the floristic variability of the region, enormous floral visits, and singular enzymes, which provides a rich and balanced therapeutic and nutritional high quality diet.
Keywords: Meliponicultura; Amazônia; composição centesimal; Compostos bioativos; CNPQ:: CIÊNCIAS AGRÁRIAS